Losses experienced by children alienated from a parent. (February 2022) - Harman, Jennifer J.; Matthewson, Mandy L.; Baker, Amy J.L.
Abstract: Parental alienation occurs when a child aligns with one parent and unjustifiably rejects the other as a result of parental alienating behaviors. This article provides an overview of current research and theory regarding the losses alienated children endure. Parental alienating behaviors alter the child's beliefs, perceptions, and memories of the alienated parent, triggering a cascade of profound losses for the child. These losses include loss of individual self, childhood experiences, extended family, community, and activities and relationships essential for healthy development. Consequently, alienated children often experience ongoing and ambiguous losses and thereby suffer disenfranchised grief in isolation. Highlights: Parental alienating behaviors are related to a child's rejection of a parent for unjustified reasons. Children who have been alienated from a parent experience substantial losses across many areas of their lives. The alienated child's loss of the parent-child relationship is often compounded by the loss of important social supports.